Public Information Disclosure and Community Digital Literacy During a Pandemic - Anasta Novi Hidayati; Andre Noevi Rahmanto; Albert Muhammad Isrun Naini (PT FORMOSA CENDEKIA GLOBAL, 2023)
One of the government's obligations is to provide public information to the public in order to maintain democratic stability and realize public-oriented governance. Efforts to provide good and correct information to the public include efforts to provide information about Covid-19. Because it is undeniable that widespread misleading information circulating in the public sphere of the network has generated debate about its potential dangers to democracy, organizations and individuals. However, as part of the information society and digital society, we are not only passive in receiving information. There must be digital literacy in terms of receiving, filtering, disseminating and producing information that has implications for the public. There are several digital literacy competencies that we must have, because now we live in a digital era, therefore we must improve our good digital literacy skills, not only being able to operate tools, but also being able to use digital media with full responsibility